Specifics of temperature extremes under the conditions of urban climate - STŘEDOVÁ, Hana; FUKALOVÁ, Petra; ROŽNOVSKÝ, Jaroslav (Contributions to Geophysics and Geodesy, 2010)
Urban climate causes intensive physical stress with negative impacts on health. One of the main risk factors is incidence of long-term period of high temperatures during the summer months, so-called heat waves. As a heat wave, a period of at least 3 consecutive days with maximum daily air temperature ≥ 30 °C was considered. In this paper the heat-wave incidence and its dynamics are defined in the long-term monitoring in the cadastral of Brno. To determine the impact of urban heat island on observed characteristics, the temperature data series directly affecting the urban environment and temperature data series of non-urban area were evaluated. Urban climate is represented by Brno-Zabovresky station, and sub-urban climate by Brno-Turany station. Results are presented for the longest possible period, i.e. since 1987 when measurements in Zabovresky began till 2008 (22 years). For the evaluation, the homogenized data of daily maximum air temperature was used. The basis of the data was obtained by measurement at CHMI station network. The longest average length of the heat wave was recorded in 1994 (Zabovresky and Turany 8 days). The longest maximum length of the heat wave was recorded in 1994 (Zabovresky 19 days, Turany 17 days). The maximum number of heat waves per year was 6 at the station Brno-Zabovresky and 4 at Turany (1992, 1998 – Zabovresky and 2003 – Turany). The results showed significant specifics of urban climate as compared to suburban areas.